Pierwotne i wtórne delegowanie kompetencji w wielopoziomowym systemie zarządzania Unii Europejskiej - RUSZKOWSKI, JANUSZ (Rocznik Integracji Europejskiej, 2012)
The study was prepared on the basis of the Principal-Agent Theory (PAT) and a method that is associated with it. This choice resulted from the major trajectories in the delegation processes, established on the one hand by states playing the role of principals, and on the other – by supranational institutions in their role as agents. The delegation theory explains the relationship between an entity that delegates power and that which is delegated (the receiving power) and helps analyze the phenomenon of the transfer of power between those entities, its reasons, circumstances, stages of the process, the outcomes and proper terminology and typology. This approach is, therefore, based and focused on the theoretical achievements in the area of research into the process of delegating. The delegation theory is actually the focal plane of theoretical approaches concerning delegating with the elements of the selection of the methods and logic of explanation, and so on. In addition to the clarification of the term of delegation of power and its stages, two basic types of delegation are examined, namely: primary and secondary delegation, and their derivatives, including the relationships between them in the multi-level governance of the European Union.